Bretton Woods 2 is dead, long live Bretton Woods 3? - Jörg Bibow (Levy Economics Institute of Bard College, 2010)
This paper sets out to investigate the forces and conditions that led to the emergence of global imbalances preceding the worldwide crisis of 2007-09, and both the likelihood and the potential sustainability of reemerging global imbalances as the world economy recovers from that crisis. The 'Bretton Woods 2' hypothesis of sustainable global imbalances featuring a quasi-permanent U.S. current account deficit overlooked that the domestic counterpart to the United States' external deficit-soaring household indebtedness-was based not on safe debts but rather toxic ones. We critique the 'global saving glut' hypothesis, and propose the 'global dollar glut' hypothesis in its stead. With the U.S. private sector in retrenchment mode, the question arises whether fiscal expansion might not only succeed in filling the gap in U.S. domestic demand but also restart global arrangements along BW2 lines, albeit this time based on public debt-call it 'Bretton Woods 3.' This paper explores the chances of a BW3 regime, highlighting the role of 'dollar leveraging' in sustaining U.S. trade deficits. Longer-term prospects for a postdollar standard are discussed in the light of John Maynard Keynes's 'bancor' plan.
Keywords: E12; E58; E65; F33; 330; reserve currency; global monetary order; global saving glut; global dollar glut; global crisis